2014
DOI: 10.1128/aac.03039-14
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Multidrug-Resistant Campylobacter Species Isolates with a Horizontally Acquired rRNA Methylase

Abstract: Antibiotic-resistant Campylobacter constitutes a serious threat to public health, and resistance to macrolides is of particular concern, as this class of antibiotics is the drug of choice for clinical therapy of campylobacteriosis. Very recently, a horizontally transferrable macrolide resistance mediated by the rRNA methylase gene erm(B) was reported in a Campylobacter coli isolate, but little is known about the dissemination of erm(B) among Campylobacter isolates and the association of erm(B)-carrying isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
140
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(158 citation statements)
references
References 33 publications
12
140
3
3
Order By: Relevance
“…These results indicate that the aph(2Љ)-If-containing segment is inserted in a conserved location on the chromosome and is widely spread in the gentamicin-resistant Campylobacter isolates in China. (14), and the genomic islands harboring aminoglycoside resistance and multidrug resistance were identified between cadF and CCO1582 on the chromosome in C. coli (16,22). In the present study, multiple aminoglycoside resistance genes and a cat gene are found to be located in a novel spot between Cj0299 and panB, which has never been reported previously.…”
Section: Resultssupporting
confidence: 51%
“…These results indicate that the aph(2Љ)-If-containing segment is inserted in a conserved location on the chromosome and is widely spread in the gentamicin-resistant Campylobacter isolates in China. (14), and the genomic islands harboring aminoglycoside resistance and multidrug resistance were identified between cadF and CCO1582 on the chromosome in C. coli (16,22). In the present study, multiple aminoglycoside resistance genes and a cat gene are found to be located in a novel spot between Cj0299 and panB, which has never been reported previously.…”
Section: Resultssupporting
confidence: 51%
“…Macrolide resistance among Campylobacter jejuni and Campylobacter coli strains is generally much more severe in developing countries than in developed countries (5)(6)(7)(8)(9). In addition, there is a much higher frequency of macrolide resistance in C. coli than that in C. jejuni, both in isolates derived from humans and in those from food animals (6,10,11).…”
mentioning
confidence: 99%
“…In addition, there is a much higher frequency of macrolide resistance in C. coli than that in C. jejuni, both in isolates derived from humans and in those from food animals (6, 10, 11). Very recently, the rRNA methylase Erm(B) has emerged as an important mechanism of acquired macrolide-lincosamide (ML) resistance in C. jejuni and C. coli (8,12,13), the two most common human disease-causing Campylobacter species. In Gram-positive bacteria, the expression of erm genes can be either constitutive or inducible (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A resistência de alto nível a eritromicina pode estar relacionada à presença do gene erm, o qual pode estar associado com ilhas de resistência multidrogas cromossômicas ou de plasmídeos transferíveis (WANG et al, 2015;EFSA, 2017 Os mecanismos atribuídos à resistência à tetraciclina estão relacionados ao efluxo, por meio da diminuição da acumulação da droga no interior da célula;…”
Section: Resistência Aos Macrolídeosunclassified